1997
DOI: 10.1073/pnas.94.20.10913
|View full text |Cite
|
Sign up to set email alerts
|

A single in vivo administration of bombesin antagonist RC-3095 reduces the levels and mRNA expression of epidermal growth factor receptors in MXT mouse mammary cancers

Abstract: Epidermal growth factor (EGF) and its receptors (EGFR) play important roles in tumorigenesis. In various experimental cancers, treatment with antagonists of bombesin͞ gastrin-releasing peptide (BN͞GRP) produces a reduction in EGFRs, concomitant to inhibition of tumor growth. To investigate the mechanisms involved, we monitored concentrations of BN͞GRP antagonist RC-3095 in serum of mice, rats, and hamsters given a single subcutaneous or intravenous injection of this analog. In parallel studies, we measured lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…In accord with our previous findings in MDA-MB-231 and MDA-MB-468 human mammary tumors and MXT mouse mammary cancers (11,12,14), the treatment with our BN͞GRP antagonists RC-3095 and 3940-II results in a marked reduction in growth of MDA-MB-435 human mammary cancers in nude mice. RC-3940-II at doses of 10 g͞day proved to be more powerful than RC-3095 at 20 g͞day.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In accord with our previous findings in MDA-MB-231 and MDA-MB-468 human mammary tumors and MXT mouse mammary cancers (11,12,14), the treatment with our BN͞GRP antagonists RC-3095 and 3940-II results in a marked reduction in growth of MDA-MB-435 human mammary cancers in nude mice. RC-3940-II at doses of 10 g͞day proved to be more powerful than RC-3095 at 20 g͞day.…”
Section: Discussionsupporting
confidence: 78%
“…Accordingly, in addition to decreasing the levels of EGFR, as it was reported in previous studies (11)(12)(13)(14), BN͞GRP antagonists also induce down-regulation of other members of the ErbB͞ HER family. The expression of mRNA for EGFR and HER-2, -3, and -4 in general was well correlated with receptor protein levels, although Western blot analyses revealed a somewhat greater decrease in HER-2 and HER-3 protein levels after treatment with BN͞GRP antagonists.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Indirect evidence suggests the potential involvement of EGFR in GRP or BLP signaling. In several in vivo tumor models (including SCLC and estrogen-dependent and estrogen-independent MTX mouse mammary cancers), treatment with a synthetic bombesin/GRP antagonist, RC-3095, resulted in the downregulation of EGFR mRNA expression levels (Pinski et al, 1994;Halmos and Schally, 1997;Szepeshazi et al, 1997;Koppan et al, 1998). Moreover, Liebow et al showed that bombesin and EGF seemed to promote phosphorylation of similar substrates (Liebow et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…BN/GRP antagonists synthesized in our laboratory have already been shown to be effective against a wide range of solid tumors, including SCLC; breast, ovarian, and prostatic cancers; renal cell carcinomas; and brain tumors (2, 7, 21) Although pseudononapeptide BN/GRP antagonists are rapidly eliminated from the blood stream after a single administration, EGF-Rs remain down-regulated for many hours (2,22). This finding explains how daily single injections of the antagonists can maintain tumor growth inhibition (2,22). An antiproliferative effect of BN/GRP antagonists against NSCLC has not been demonstrated previously (2, 7).…”
Section: Discussionmentioning
confidence: 99%